The prevalence of tinnitus and the relationship with neuroticism in a middle-aged UK population - McCormack, Abby; Edmondson-Jones, Mark; Fortnum, Heather; Dawes, Piers; Middleton, Hugh; Munro, Kevin J.; Moore, David R. (Elsevier, 2014)
Background: Previous research has suggested that a substantial proportion of the population are severely affected by tinnitus, however recent population data are lacking. Furthermore, there is growing evidence that the perception of severity is closely related to personality factors such as neuroticism.